2003
DOI: 10.1093/ajcn/78.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and iodine supplementation of rural Tibetan children affected by Kashin-Beck osteoarthropathy

Abstract: The results of this study do not rule out the possibility that selenium may help to prevent the occurrence of Kashin-Beck disease. However, selenium supplementation had no effect on established Kashin-Beck disease, growth, or thyroid function once iodine deficiency was corrected. These results suggest that iodine, but not selenium, deficiency should be corrected in Tibetan children with Kashin-Beck disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(70 citation statements)
references
References 21 publications
2
62
0
6
Order By: Relevance
“…The geographical distribution of selenium ranges from selenium-deficient regions in China, including areas from the northeast to southwest and southeast Siberia (2,3,13,14), to selenium-rich regions in Ireland, Israel, northern Australia and the western US (15). Differences in selenium dietary intake become serious at the top of the ground food chain.…”
Section: Selenium Status and Its Biological Actionsmentioning
confidence: 99%
“…The geographical distribution of selenium ranges from selenium-deficient regions in China, including areas from the northeast to southwest and southeast Siberia (2,3,13,14), to selenium-rich regions in Ireland, Israel, northern Australia and the western US (15). Differences in selenium dietary intake become serious at the top of the ground food chain.…”
Section: Selenium Status and Its Biological Actionsmentioning
confidence: 99%
“…While it has been showed that alterations in the expression of collagen type X (ColX) and parathyroid hormone related peptide, was compatible with Kashin-Beck osteoarthropathy, due to selenium and iodine deficiency 10 . Moreover, it has been reported that selenium may help prevent the occurrence of Kashin-Beck osteoarthropathy 11 . Additionally, modifiable metabolic risk factors may lead to raised cartilage loss.…”
Section: Jfsf 46mentioning
confidence: 99%
“…Second, there has been great success using Se supplementation to prevent and control KBD [9,[14][15][16][17]. However, some scientists consider that the environmental low Se was only an external condition but not the initial etiology causing KBD [18,19].…”
Section: Introductionmentioning
confidence: 99%